Daya Tarik Wisata Moskow dalam Itinerary Perjalanan ala Backpacker Pemegang Paspor Indonesia - Pitaya Pitaya (Sekolah Vokasi, Universitas Gadjah Mada, 2017)
For most Indonesian citizen, Russia is one of the most famous country in the world. It is referred as big, far, and associated with communism. In the matter of tourism point of view Russia is always considered as one of the most attractive destination with the unique and thematic touristic atmosphere around it’s corner. But it is a fact that traveling to Russia is not easy for many tourist, specially Indonesian passport holder. There is still a confusion regarding to how to manage a travel plan, itinerary design, visa application, accommodation and other basic traveling needs. This paper gives information to any Indonesian passport holders who willing to proceed their aim to travel to Russia. It describes a process to design an itinerary of traveling to the one of Russia’s amazing tourism destination, Moscow. The methods using in this research are involving field observation and literature studies. The result shows that Moscow, as the main Russia’s tourist destination proved as the city consists with many attractions, accessibilities, a lot of amenities and supporting atmosphere for the backpacker tourist.